The little mermaid [videorecording (Blu-Ray + DVD)] - Menken, Alan (Walt Disney signature collection., 2019)
Ariel is a fun-loving and mischievous mermaid who is enchanted with all things human. Disregarding her father's order to stay away from the world above the sea, she swims to the surface and, in a raging storm, rescues Prince Eric, the man of her dreams. Determined to be human, she strikes a bargain with the devious sea witch, Ursula, and trades her fins and beautiful voice for legs. With her best friend Flounder, and her reluctant chaperon Sebastian at her side, Ariel must win the prince's love and save her father's kingdom.